A Markov Based Detection for Broadband over Power Line Communications (PLC) - Morshed, M; Sarker, P; Roy, RC (Bangladesh Journal of Scientific and Industrial Research, 2010)
Successful development of Broadband over Power Lines (BPL) is obviously a potential solution for wireless communication systems with the existing infrastructure. Multi-Carrier Code Division Multiple Access (MC-CDMA) with Orthogonal Frequency Division Multiplexing (OFDM) modulation technique is a promising solution for a frequency selective fading with impulsive noises of the PLC channel. A linear iterative receiver with a Finite State Markov Channel (FSMC) model is proposed to remove Multiple Access Interference (MAI) and Inter Symbol Interferences (ISI). In this paper we focused on Maximum Likelihood (ML) feedback detection by introducing FSMC to get significant improvement in Bit Error Rate (BER). This model of the receiver is more robust against Gaussian colored and impulsive noises of the PLC channel. Keywords: FSMC; MC-CDMA; OFDM; MAI; ISI DOI: 10.3329/bjsir.v44i4.4595 Bangladesh J. Sci. Ind. Res. 44(4), 441-444, 2009